Kursi sebagai Simbol Transisi Dampak Negatif Kehidupan Manusia pada Karya Seni Patung Kontemporer - Irvan, Muhammad; Widiarti, Lisa (Lembaga Yasin AlSys, 2023)
The journey of life that humans go through is a long journey, full of twists and turns and through stages that will surely become a process of growth and development from time to time. Because there are negative things, the impact on his life is caused by individual, family, environmental, social, cultural, political, educational and other factors. In the embodiment of the work, the chair is used as a symbol of the negative impacts that occur on human life starting from the infant phase to the elderly. There are several stages carried out in accordance with the method used in making the work, namely: preparation is observing the environment and preparing the tools and materials used in the work, Elaboration is the manufacturing stage that solidifies the main ideas related to the title, Synthetic is the sketching stage, Relations The concept is the stage of the work process and completion is the final stage in the work. Description of the work consisting of 7 works where each work is given a different title, namely: (1) infancy, (2) childhood, (3) childhood, (4) adolescence, (5) childhood young adults, (6) old adults, and (10) elderly people. The work will be exhibited for 2 days, and carry out the recording, as well as the production report.